Microrna-122 as a biomarker associated with oxidative stress in patients suffering from metabolic diseases - Reda, Ruqaya S; Khinteel Jabbar, Nawal (Vojenské zdravotnické listy, 2024)
Background: Recent evidence has shown that circulating microribonucleic acid (miRNA) has been related to many diseases either as an inhibitor or a stimulant factor, among them miRNA-122 which has proven through studies its relationship with insulin resistance, an adversative lipid profile, obesity, type 2 diabetes, and metabolic syndrome in several studies; however, the mechanisms involved are unknown. This study investigates the role of miRNA-122 expression in overweight patients suffering from metabolic disorders such as diabetes and hypertension and its relationship to the development of oxidative stress in patient groups.Materials and Methods: 30 patients with type 2 diabetes mellitus (T2DM), 30 people with hypertension (HTN), 30 patients with T2DM+HTN, and 30 healthy persons who served as controls were enrolled in this study. An ARCHITECT c4000 clinical chemistry analyzer was used to assess lipid profiles. The sandwich immunodetection approach was used to assess whole blood hemoglobinA1c. By colorimetric methodology, catalase activity (CAT), superoxide dismutase activity (SOD), malondialdehyde (MDA) levels, and advanced oxidation protein products (AOPPs) levels were measured. The expression of serum miRNA-122 was determined using the quantitative polymerase chain reaction.Results: The activity of SOD and CAT in patient groups was found to be substantially lower than in the control group (p < 0.05), whereas MDA and AOPP concentrations were found to be significantly higher in patient groups compared to the control group (p < 0.05). When patient groups were compared to control groups, the miRNA-122 level was higher in the patients (p< 0.05).Conclusions: miRNA-122 expression is involved in the pathogenesis of T2DM and HTN-induced oxidative stress, there is a reciprocal relationship between the increase in gene expression of the miRNA-122 and the increase in oxidative stress accompanied by a decrease in the effectiveness of antioxidant enzymes, which leads to the development of the disease.
Keywords: dospělí; Superoxide Dismutase; Advanced Oxidation Protein Products; Blood Chemical Analysis; biologické markery; oxidační stres; produkty pokročilé oxidace proteinů; Biomarkers; Adult; superoxiddismutasa; Oxidative Stress; lidé; biochemická analýza krve; metabolické nemoci; Malondialdehyde; mikro RNA; Metabolic Diseases; malondialdehyd; lidé středního věku; MicroRNAs; Middle Aged; Humans